Organic Pollutant Biodegradation by an Immobilized Mixed Bacterial Culture : Biodegradasi Polutan Organik oleh Kultur Bakteri Campuran Amobil - Edwan K; Qomarudin Helmy (Jurnal Teknik Lingkungan, 2022)
Pollution of organic compounds in rivers is generally contributed by wastewater discharge from human activities e.g. untreated black- & greywater, livestock farming, and industry. Without proper control of this waste generation, the river ecosystem will suffer if just rely on its self-purification and dilution by natural runoff to reduce the downstream effect. This research aimed to treat organic wastewater with an immobilized mixed bacterial culture. Immobilization was carried out using calcium alginate in a form of macrocapsule/beads, allowing the degrader microbe to be entrapped in its matrix thus preventing it from washout from the system.  3% (w/v) sodium alginate was mixed with 5 mg (dry) mixed culture and dropwise on 4% (w/v) calcium chloride solution. The results showed that immobilized microbes were still able to grow despite being entangled in a calcium alginate matrix with an initial growth of 6.1 x 105 to 7.4 x 107 colonies/grams and reduced COD content up to 68.3%. Degrader microbe immobilization offers considerable advantages compared to free/ suspended cell system due to the influence of river water flow.